Combating multidrug-resistant Helicobacter pylori with moenomycin A in combination with clarithromycin or metronidazole - Tseng, Yen-Yu; Liou, Jyh-Ming; Cheng, Wei-Chieh; Hsu, Jing-Ting; Hsu, Tsui-Ling; Wu, Ming-Shiang; Wong, Chi-Huey (Frontiers in Chemistry, 2022)
Current treatment of Helicobacter pylori involves a triple therapy comprising one proton pump inhibitor and two other antibiotics; however, the outcomes are limited due to the existence of antibiotic resistant strains. We previously reported that moenomycin A, a cell-wall transglycosylase inhibitor, is highly active against multidrug-resistant Helicobacter pylori. Herein we show that combination of moenomycin A with the protein synthesis inhibitor clarithromycin or metronidazole can synergistically achieve almost 95% eradication of multidrug-resistant Helicobacter pylori. We also found that the moenomycin A-non-susceptible strains of Helicobacter pylori with deletion of transglycosylase exhibit moenomycin A hyposensitivity, faster growth and impaired biofilm formation compared to the parental strain. Overall, the combination of moenomycin A and clarithromycin or metronidazole to achieve a synergistic effect on different targets is a promising treatment for multidrug-resistant Helicobacter pylori.